Prevalence of Antenatal Care Practice among Marginalized Community of Nepal - Sangroula, Raj Kumar (Europasian Journal of Medical Sciences, 2020)
Background: The government of Nepal aims to improve the health of mothers and newborns by providing quality safe motherhood services. Increasing access and utilization of antenatal care (ANC) services are the first steps towards improving maternal and neonatal health outcomes, particularly those of the marginalized communities. Objective: The aim of this study is to assess the prevalence and factors associated with the antenatal care visits among the marginalized community of Nepal. Methods: A mixed-method study was conducted among 202 reproductive aged females of marginalized community in Nepal having childbirth during the last 2 years. Pre-tested semi-structured questionnaires and key informant interview guidelines were used for the collection of data. Bivariate and multiple regression analysis were carried out to find out the factors associated with the antenatal care visits. For qualitative data, thematic analysis was done. Results: More than half (56.9%) of the participants had completed four or more antenatal care visits. Mothers with primary level of education were 2.7 times more likely to complete four or more ANC visits (AOR: 2.7, CI: 1.09-7.07). Age at marriage (AOR: 2.3, CI: 1.08-5.22), women who took decisions alone for their health (AOR: 2.9, CI: 1.22-6.96),exposure to FCHV (AOR:2.5, CI: 1.1-5.9), knowledge about safe delivery incentive program (AOR: 3.6, CI: 1.46-9.0) and perception of “good quality” ANC service(AOR:7.5, CI: 3.3-17.1)were significantly associated with the number of ANC visits. Conclusion: The overall utilization of antenatal health services was low. So, there is a need of different community based maternal health programs especially targeting the marginalized females.